Molecular and structural characterization of MHC Class II β genes reveals high diversity in the cold-adapted icefish chionodraco hamatus - Gerdol M.; Lucente D.; Buonocore F.; Poerio E.; Scapigliati G.; Mattiucci S.; Pallavicini A.; Cimmaruta R. (Scientific Reports, 2019)
This study reports the presence of two distinct MHC class II β genes in the Antarctic icefish Chionodraco hamatus, belonging to the classical (ChhaDAB) and nonclassical (ChhaDBB) evolutionary lineages. By the application of targeted sequencing approach, a remarkable molecular diversity in the exon 2 sequence of the highly expressed gene ChhaDAB has been observed, resulting in an estimate of 92 different variants translated in 87 different peptides from 54 analysed icefish individuals. A highly conservative estimate, based on a 95% sequence identity threshold clustering, translate this variability in 41 different peptide clusters belonging to four different clades and showing the signature of different kinds of selection. In stark contrast, the poorly expressed ChhaDBB gene displayed a very low level of molecular diversity within exon 2, in agreement with expectations for a nonclassical MHC class II β gene.